Mean glycosylated hemoglobin in children with type 1 diabetes at King Fahad Medical City, Riyadh, Saudi Arabia - Abdulhameed Y Alsaheel; Sulaiman I Alayed; Yazzan M Alotaibi; Aseel A Alfahhad; Othman M Alothman; Hissah F Alnefaie (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND: Type 1 diabetes is the third most common chronic disease among teenagers. In Saudi Arabia, there is a gap of knowledge regarding hemoglobin A1C (HbA1c) concentration levels, and adherence to regular follow-up visits by patients. The aim of this study was to determine the mean glycosylated hemoglobin (HbA1c) levels in diabetic children who have been diagnosed with type 1 diabetes and were being followed up at a tertiary care center in Saudi Arabia. MATERIALS AND METHODS: This cross-sectional study was conducted among all diabetic children treated at King Fahad Medical City (KFMC) in Riyadh, Saudi Arabia. Data were retrieved and analysed during the period from September to December 2018. Diabetic patients of <18 years and who were being followed up at KFMC were included in the study. Data on age, sex, duration of illness, associated comorbidities, antidiabetic regimen, and HbA1c levels were obtained. Student t-test was used to compare quantitative parameters between two groups, and Chi-square employed to test for associations between categorical variables at 5% significance level. RESULTS: A total of 510 patients of were included in the study; about 53% were females. The mean HbA1c level was 10.6% and females showed higher HbA1c levels. Data showed a strong correlation between age and HbA1c levels (P < 0.001), with older patients showing higher HbA1c levels. The HbA1c levels also increased as the duration of disease increased. The median number of patient visits to KFMC was two per year. No statistically significant differences were observeed for type of treatment for diabetes. Celiac disease, the most frequent comorbidity, was seen in 50% of patients. CONCLUSION: Diabetic children who were followed up at KFMC had high HbA1C level (10.6%), and lower than recommended follow-up visits per year. The treating physicians should educate patients and their legal guardians on the importance of follow-up visits and their role in controlling HbA1C levels, and following healthier lifestyle.